2001
DOI: 10.1165/ajrcmb.25.4.4578
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Calcium-Activated Chloride Channel as a Shared Target of Th2 Cytokine Pathways and Its Potential Involvement in Asthma

Abstract: Interleukin (IL)-9 is a T helper (Th) 2 cytokine recently implicated as an essential factor in determining susceptibility to asthma. Transgenic mice overexpressing IL-9 exhibit many features that are characteristic of human asthma. To better understand the mechanism by which IL-9 mediates the various biologic activities in asthma, we performed suppressive subtraction hybridization with whole lung from IL-9 transgenic and control mice. Here we report the identification of mCLCA3, a calcium-activated chloride ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
99
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 30 publications
11
99
2
1
Order By: Relevance
“…Recent studies have shown that all subunits of hCLCA1 and mCLCA3 are secreted soluble proteins rather than being trans-membrane proteins [7,23]. Expression of hCLCA1 or mCLCA3 was found to be up-regulated following exposure to respiratory tract irritants that are responsible for a Th2 local inflammation [26,34]. It has been shown that at transcript and protein level, expression of hCLCA1 was up-regulated by IL-13 in normal human bronchial epithelial cells in vitro [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that all subunits of hCLCA1 and mCLCA3 are secreted soluble proteins rather than being trans-membrane proteins [7,23]. Expression of hCLCA1 or mCLCA3 was found to be up-regulated following exposure to respiratory tract irritants that are responsible for a Th2 local inflammation [26,34]. It has been shown that at transcript and protein level, expression of hCLCA1 was up-regulated by IL-13 in normal human bronchial epithelial cells in vitro [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that at transcript and protein level, expression of hCLCA1 was up-regulated by IL-13 in normal human bronchial epithelial cells in vitro [33]. Whether the secretion of the ovine CLCA protein has a direct or indirect function in worm expulsion remains unknown, although hCLCA1 has been associated with an increase in mucus production following a Th2 response of the respiratory tract [34]. Furthermore, increased expression of IL-9 resulted in increased expression of hCLCA1 mRNA by epithelial cells in patients suffering from asthma [31] suggesting that hCLCA1 may be responsible at least in part for the overproduction of mucus by the asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, niflumic acid, a broad inhibitor of anion transport, suppresses the development of asthma in mice (12). Previous reports showed that Th2-type cytokines including IL-13 induce expression of gob-5 (mCLCA3), which had been thought to be a chloride transporter, suggesting a critical role for gob-5 in mucus overproduction in bronchial asthma (13,14). However, the role of gob-5 in asthma remains somewhat elusive at the moment, because this transporter is indeed a secretory, but not transmembrane, protein (15).…”
mentioning
confidence: 81%
“…8,9 Recently, a mouse model of asthma provided the evidence that the gob-5 gene is involved in the pathogenesis of asthma. 10,11 Nakanishi et al reported that intratracheal administration of adenovirus-expressing antisense gob-5 RNA into AHR-model mice efficiently suppressed the asthma phenotype, including AHR and mucus overproduction, and that an adenovirusmediated overexpression of gob-5 in airway epithelia exacerbated the asthma phenotype. Zhou et al 11 showed that gob-5 is highly expressed in the lung epithelium of IL-9 transgenic mice, which exhibit many signs and symptoms characteristic of human asthma.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Nakanishi et al reported that intratracheal administration of adenovirus-expressing antisense gob-5 RNA into AHR-model mice efficiently suppressed the asthma phenotype, including AHR and mucus overproduction, and that an adenovirusmediated overexpression of gob-5 in airway epithelia exacerbated the asthma phenotype. Zhou et al 11 showed that gob-5 is highly expressed in the lung epithelium of IL-9 transgenic mice, which exhibit many signs and symptoms characteristic of human asthma. Asthmatic patients showed upregulation of hCLCA1 (human calcium-dependent chloride channel-1) mRNA in mucusproducing epithelium responsive to the interleukin IL-9.…”
Section: Introductionmentioning
confidence: 99%